A plain man looks at the cross an attempt to explain in simple language for the modern man, the significance of the death of Christ - Weatherhead, Leslie D. (London, UK Independent, 1957)
Includes bibliographical references.
First ed. published 1945
Keywords: Jesus Christ -- death